Kombinasi WhatsApp dan Google Classroom dalam Pembelajaran Matematika Mata Kuliah Aljabar Elementer - Fadhil Zil Ikram; Rosidah Rosidah (Universitas Negeri Makassar, 2023)
Learning mathematics during the pandemic has many challenges such as internet constraints, be it network quality or limited internet quota owned by students or students. This research uses a sequential explanatory design to investigate the effectiveness of the combined use of WhatApp (WA) and Google Classroom (GC) in learning mathematics, especially in the Elementary Algebra course. The sampling technique used was simple random sampling and the selected class was class A which is one of the classes from one of the universities in South Sulawesi. Related to qualitative data, surveys and interviews were conducted to find out how students respond to the implementation of the use of the two applications and why the use of the two applications is effective / ineffective in mathematics learning. The results showed that the mean of the class scores is 80.12 with a standard deviation of 1.85. Based on inferential analysis, combination of WA and GC in learning mathematics in the Elementary Algebra course was effective. In addition, most students gave positive responses. Based on students' perspectives, the ease of access, features of both applications and ease of use are the reasons for the success of mathematics learning using WA and GC.